Content Analysis of Environmental Awareness Messages in Bumantara Team Tiktok Content - Vawana, Ande; Iva Fikrani Deslia (Jogjakarta Communication Conference (JCC), 2024)
Technological developments can provide convenience in every activity carried out by humans if used wisely and correctly. In this millennial era, anyone can use it. Social media can be a place to convey information, including positive messages. Social media that is used well can benefit existing conditions around us. One is environmental awareness, which is carried out by the Bumantara Team community on their TikTok account. Bumantara Team is a community of five young people. They use the TikTok platform to spread messages about the importance of keeping the environment clean and have succeeded in mobilizing many people to participate in clean-up actions. Qualitative research methods in this study used content analysis to understand the messages conveyed by the Bumantara Team through their TikTok account, with a focus on awareness of environmental cleanliness. The theory used as an analytical tool is message studies. Message studies is a message analysis model based on critical theory. Thus, this research provides insight into how social media can be used positively in addressing environmental problems.